Radiosynoviorthesis in children with haemophilia - Pasta, G.; Mancuso, M. E.; Perfetto, O. S.; Solimeno, L. P. (Hämostaseologie, 2009)
Recurrent bleeding into joints represents the clinical hallmark of haemophilia and, if not adequately treated, it may cause chronic synovitis and degenerative arthropathy. The first treatment option of recurrent haemarthroses and/or chronic synovitis is represented by synoviorthesis, both chemical and radioisotopic, with a success rate of approximately 80% for both. However, radioisotopic synoviorthesis should be preferred because it makes it possible to obtain complete synovial fibrosis usually in one session, without the need for repeated injections, thus reducing the risk of bleeding complications and concentrate consumption. For all these reasons this procedure should be implemented and supported, particularly in developing countries.
Keywords: Synoviorthesis; haemophilia